Family law and citizenship: the case study of Egyptian Baha'is - Dana, Vargha (AUC Knowledge Fountain, 2014)
After a four-year legal battle in 2009, Egypt’s Supreme Administrative Court granted Egyptian Baha’is the right to obtain national identification cards. However, members of this minority group have continued to struggle to access basic rights of citizenship. Non-recognition of Baha’i marriage is the chief source of disenfranchisement of Baha’is in Egypt. This study argues that marriage as the legal instrument of creating a family, can act as the precursor to citizenship. By sanctioning certain types of marriages and prohibiting others, the state translates its specific ideology into creation of politicized legal entities known as citizens. The state’s aspiration is to create an ideal nation by embracing “normal” families that can produce ideal citizens. As a vehicle for public policy, marriage has the capacity to act as a powerful hegemonic tool that shapes the society on the bases of class, gender, race, and religion. The family is fundamentally a legal entity shaped and sanctioned by the state and it is the site of production and reproduction of citizenship.